IMPLEMENTASI PERATURAN PRESIDEN NOMOR 76 TAHUN 2020 TENTANG PENGEMBANGAN KOMPETENSI KERJA MELALUI PROGRAM KARTU PRAKERJA DI KABUPATEN BEKASI - M. Yunus; Sherly Mutia Ivanka (Halu Oleo University, 2024)
This research explores the implementation of the Pre-Employment Card Program in Bekasi Regency based on Presidential Regulation No. 76 of 2020. The implementation of the pre-employment card program has experienced various problems, including failing to register, failing to participate because the quota has been met, failing to connect to an account, problems in training such as certification that is difficult to issue, and finally funds that fail to be disbursed. The research objectives are to analyze the implementation of the regulation, identify inhibiting factors, and evaluate community perceptions. The qualitative research method with case studies involved observation and in-depth interviews. The results of this study indicate that the Implementation of the Pre-Employment Card Program in Bekasi Regency has been running quite well but there are still obstacles to the Population Identification Number when registering and also there are still many people in Bekasi Regency who are unfamiliar with technology or social media. The public perception of the pre-employment card program is a program that provides free training, certificates, and incentives. The pre-employment card program is very useful and helps the community because it is a program that is devoted to increasing community competence or skills. Due to the covid-19 pandemic, the government provided incentive funds to the community of 600 thousand per person after completing all training.